Autoregulation of a Personality under the Conditions of Pedagogues’ Preparation to Professional Activity - Kateryna Lysenko-Gelemb’yuk (Pedagogical Discourse, 2012)
This article is devoted to the study of psychological autoregulations functions  and their influence to interpersonal conflict solving. The views of different scientists on this phenomenon have been analysed. The focus of attention is based on the theoretico-psychological faset.